2021
DOI: 10.20538/1682-0363-2021-2-36-43
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of conjunctival and scleral regeneration after intraoperative application of cyclosporin A solution in rabbits with steroid-induced glaucoma

Abstract: Цель. В эксперименте in vivo изучить влияние местной интраоперационной аппликации 0,05%-го раствора (р-ра) циклоспорина А на регенерацию конъюнктивы и склеры после операции на глазах кроликов со стероидной глаукомой.Материалы и методы. На I этапе эксперимента 29 самцам кроликов калифорнийской породы моделировали стероидную глаукому путем введения под конъюнктиву обоих глаз 0,5 мл 0,4%-го р-ра дексаметазона 1 раз в нед в течение 3 мес (12 инъекций). На II этапе эксперимента, после развития стероидной глаукомы, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…An in vivo study by Park et al showed that postoperative topical 2% cyclosporine can enhance the effectiveness of glaucoma drainage implant surgery measured by IOP and improve the flow resistance through the implant capsule, although there was no difference in fibroblast density [ 76 ]. Recent in vivo studies with different delivery methods and concentrations have supported this data [ 174 , 175 ]. However, 2% cyclosporine intraoperatively and postoperatively was not associated with IOP or prolonged bleb survival in rabbits when compared with MMC [ 176 ].…”
Section: Strategies To Prevent Ocular Fibrosis Following Glaucoma Fil...mentioning
confidence: 75%
“…An in vivo study by Park et al showed that postoperative topical 2% cyclosporine can enhance the effectiveness of glaucoma drainage implant surgery measured by IOP and improve the flow resistance through the implant capsule, although there was no difference in fibroblast density [ 76 ]. Recent in vivo studies with different delivery methods and concentrations have supported this data [ 174 , 175 ]. However, 2% cyclosporine intraoperatively and postoperatively was not associated with IOP or prolonged bleb survival in rabbits when compared with MMC [ 176 ].…”
Section: Strategies To Prevent Ocular Fibrosis Following Glaucoma Fil...mentioning
confidence: 75%